2013
DOI: 10.1128/ec.00214-12
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc Cluster Protein Sut1 Contributes to Filamentation in Saccharomyces cerevisiae

Abstract: bSut1 is a transcriptional regulator of the Zn(II) 2 Cys 6 family in the budding yeast Saccharomyces cerevisiae. The only function that has been attributed to Sut1 is sterol uptake under anaerobic conditions. Here, we show that Sut1 is also expressed in the presence of oxygen, and we identify a novel function for Sut1. SUT1 overexpression blocks filamentous growth, a response to nutrient limitation, in both haploid and diploid cells. This inhibition by Sut1 is independent of its function in sterol uptake. Sut1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 54 publications
(67 reference statements)
1
48
0
Order By: Relevance
“…Early Northern blotting experiments suggested that SUT1 is not expressed under aerobic conditions [8]. However, later real-time PCR and immunoblotting experiments showed that mRNA and protein are aerobically expressed and induced under anaerobic conditions, as suggested earlier [8,34,53]. Rox1 partially represses SUT1 in the presence of oxygen [8] (Figure 5).…”
Section: Regulatory Mechanismsmentioning
confidence: 72%
“…Early Northern blotting experiments suggested that SUT1 is not expressed under aerobic conditions [8]. However, later real-time PCR and immunoblotting experiments showed that mRNA and protein are aerobically expressed and induced under anaerobic conditions, as suggested earlier [8,34,53]. Rox1 partially represses SUT1 in the presence of oxygen [8] (Figure 5).…”
Section: Regulatory Mechanismsmentioning
confidence: 72%
“…The transcription factor Sut1 regulates filamentation through its targets GAT2 , HAP4 , MGA1 , MSN4 , NCE102 , PRR2 , RHO3 and RHO5 (Foster et al ., ). Under optimal growth conditions, Sut1 represses the expression of these genes, whereas under filamentation‐inducing conditions, this repression is lifted.…”
Section: Resultsmentioning
confidence: 97%
“…Next, we examined whether the newly identified targets of Ecm22 and Upc2 ( PRR2 , NPR1 and FHN1 ) play a role in filamentation. As shown before, PRR2 expression is strongly upregulated during haploid and diploid filamentation (Foster et al ., ). Furthermore, PRR2 expression correlates with filamentation phenotypes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…SUT1, which improved anaerobic cellobiose fermentation when overexpressed, is an activator of sterol uptake and hypoxic genes [75], but its regulatory role in central carbon metabolism is not known. Constitutive overexpression of SUT1 has been shown to slow growth on glucose in aerobic cultures by downregulating genes important for respiratory metabolism [76], and it was also shown to block filamentous growth [77]. HAP4, deletion of which improved anaerobic cellobiose fermentation is a regulatory subunit of the Hap2/3/4/5 complex that positively regulates respiratory gene expression, and is a hotspot of genetic variation in cell physiology between yeast strains [27].…”
Section: Discussionmentioning
confidence: 99%